2021
DOI: 10.1111/his.14318
|View full text |Cite
|
Sign up to set email alerts
|

Severe glomerular C3 deposition indicates severe renal lesions and a poor prognosis in patients with immunoglobulin A nephropathy

Abstract: Severe glomerular C3 deposition indicates severe renal lesions and a poor prognosis in patients with immunoglobulin A nephropathy Aims: Glomerular complement 3 (C3) deposition is often observed in renal biopsies of patients with IgA nephropathy (IgAN); however, the relationship between the intensity of C3 deposition and the long-term prognosis of IgAN has rarely been reported. In this retrospective study, we aimed to evaluate the prognostic value of glomerular C3 deposition for IgAN progression. Methods and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…The genotype–phenotype analysis in this study showed that patients with IgAN with the rs12614-T allele presented with high serum C3 levels and less intense mesangial C3 deposition, which were indicators of mild complement activation. Similarly, several studies found that decreased serum C3 levels and intense mesangial C3 deposition could predict the poor prognosis of IgAN ( 32 , 33 ), suggesting that the complement activation may be an essential player in the pathogenesis of IgAN. However, no association was observed between rs12614 and the renal outcome of IgAN, and a longer follow-up time may be needed for further elucidation.…”
Section: Discussionmentioning
confidence: 90%
“…The genotype–phenotype analysis in this study showed that patients with IgAN with the rs12614-T allele presented with high serum C3 levels and less intense mesangial C3 deposition, which were indicators of mild complement activation. Similarly, several studies found that decreased serum C3 levels and intense mesangial C3 deposition could predict the poor prognosis of IgAN ( 32 , 33 ), suggesting that the complement activation may be an essential player in the pathogenesis of IgAN. However, no association was observed between rs12614 and the renal outcome of IgAN, and a longer follow-up time may be needed for further elucidation.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to MPGN, C3 may be deposited in IgAN or MN. When C3 deposition was accompanied by IgAN and MN, the renal outcome was worse in cases with above-moderate C3 dominance [17][18][19]. Therefore, it is necessary to review and reclassify the primary diagnosis; due to practical problems, this should be considered a limitation of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…In IgA nephropathy, complement activation is widespread, as evidenced by approximately 90% patients with glomerular C3 deposition. 7,38 Recent novel therapies targeting complement activation showed promising effects in IgA nephropathy. 11,39,40 Glomerular complement activation in IgA nephropathy is also influenced by multiple factors and mechanisms.…”
Section: Discussionmentioning
confidence: 99%